Quantification of cardiac structure and function using transthoracic echocardiography in term women with HIV - Gibbs, Matthew Winton (Department of Anaesthesia, 2017)
Introduction: In South Africa, up to 30% of pregnant women are human immunodeficiency virus (HIV) positive and morbidity and mortality is high in this group. HIV positive men and women may have multiple cardiovascular comorbidities, which include systolic dysfunction that may progress to heart failure secondary to dilated cardiomyopathy. However the concurrent effect of pregnancy and HIV infection on haemodynamics has not been extensively researched. The aims of this study were to quantify haemodynamics using transthoracic echocardiography (TTE) in term pregnant women with HIV on antiretroviral (ARV) treatment and compare the data with term healthy women in the same population. Method: After ethics approval and written consent, 30 consecutive term HIV positive women and 40 healthy term pregnant women were recruited. HIV positive women had a CD4 count greater than 200 and were either on Highly Active Anti-Retroviral Therapy (HAART) or single drug management. Results: Haemodynamic assessment was possible in all patients and women in the two groups were similar in age, and body mass index. Mean CD4 count was 452 ± 187.8 and duration of therapy was 15.9 ± 22.4 months. Compared with healthy pregnant women, women with HIV have systolic changes exhibited by reductions in left ventricle (LV) septal and right ventricle (RV) systolic myocardial velocities as well as increased LV end-diastolic (ED) areas and diastolic changes of increased RV isovolumetric (IV) relaxation and reduced RV e′ diastolic myocardial velocities. These changes occur in the presence of a reduced LV mass. Pericardial effusions occurred more frequently and are of a larger size in women with HIV. These findings suggest subclinical impairment of systolic function in the LV as well as subclinical impairment of both systolic and diastolic function in the RV. Discussion: Transthoracic echocardiography can quantify cardiac function in healthy pregnant women and in pregnant women with HIV and is acceptable to the patients. HIV positive pregnant women at term on anti-retroviral therapy have hearts that have subclinical systolic dysfunction in the presence of decreased LV mass and increased end-diastolic areas. This may represent a failure to compensate for the increased haemodynamic demands of pregnancy and may be as a result of the direct effects of HIV itself or due to anti-retroviral drugs.